Multimodal Analysis of "Teh Pucuk Harum" - Rina Octavia simarmara; Febrika Dwi Lestari (English Teaching and Linguistics Journal (ETLiJ), 2020)
The best way to provide information as quickly and correctly that it is conveyed to consumers is a good advertising. So the buyers can see the advertisements delivered before buying something that they want. Multimodal analysis is one way how to analyze an object that we shown from a visual of it. Teh Pucuk is one of an advertisement that showing a multimodal analysis that we can see from the descriptive of the information of Teh pucuk and also about a visual design of it.KeyWords: Advertisement, Multimodal, Teh Pucuk